Motivations, Consequences, and Barriers to Using the Internet in Adult Literacy and Basic Education Classroom - Jim Berger Ph.D. (Adult Education Research Conference, 2006)
This study sought to create profiles of adult literacy and basic education (ALBE) instructors and use of the Internet in their classrooms. Two profiles were found and significant group differences were seen based on factors related to use of computers in the classroom, e-mail, and number of students served.
Keywords: Adult literacy and basic education; internet; classroom strategies